The soft side of building ISO 14001 : development of environmental employee engagement in the case of Muovilami Oy - Vainioranta, Jenni (2021)
Environmental management systems (EMSs) are important voluntary tools for companies to manage their environmental impacts and improve their environmental performance. However, EMS offer merely a framework for environmental management and, in addition, a genuine engagement of the management and employees with environmental work and its goals is a prerequisite for effective implementation of EMS and real organisational change and greening of the organisation. In recent years, employee engagement has become a popular research topic, as it has been acknowledged to ensure better performance at both employee and company level. However, there is a lack of studies focusing on environmental employee engagement, nor there is available suitable theoretical models or metrics to directly measure the level of environmental employee engagement. The aim of this study was to investigate how employees’ environmental attitudes and awareness develop while building an EMS in the case company and how the development of employees’ environmental attitudes and awareness indicate development of environmental employee engagement. Employee’s engagement was assessed by conducting environmental attitude and awareness survey and interviews before and in the late stages of building the EMS. In addition, to measure engagement, theory-based content analysis was carried out by using key concepts regarding employee engagement applicable to environmental work. Hence, the research is defined as a case study carried out as a longitudinal study, using mixed method research. According to the results, employee’s attitudinal engagement has developed to some extent, as there is an indication of the development of employees’ perceived importance of environmental work and the level of support towards the company’s environmental work. Employees behavioural engagement stayed somewhat the same level, as employee’s readiness to put more effort into environmental responsibility was similarly high before and after the EMS. There was seen some development in the cognitional engagement as the willingness to learn and participate into environmental trainings increased in some extent.